INTEGRASI PENDIDIKAN ISLAM DAN PERTANIAN MODERN DALAM KURIKULUM MAM 01 TEGALOMBO - Joko Setiono; Erwin Ardianzah; Harsono; Masduki (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study explores the integration of Islamic education and modern agriculture at MA Muhammadiyah 01 Tegalombo, highlighting how the school cultivates a holistic learning environment that harmonizes faith, knowledge, and practical skills in the era of Society 5.0. Employing a qualitative case study approach, the research was conducted in December 2025 through observation, in-depth interviews, and documentation involving school leaders, teachers, and students. Findings reveal that this integration is not merely curricular but embedded as a living culture within the madrasah community. Agricultural activities become spiritual and moral education arenas that strengthen discipline, gratitude, and environmental responsibility. Teachers and leaders act as murabbi, guides who nurture intellect and character simultaneously. Despite technological and infrastructural limitations, the madrasah demonstrates how Islamic education can adapt dynamically to modernity while maintaining its spiritual essence. This study concludes that such integration fosters insan kamil, morally grounded, independent, and socially responsible individuals capable of facing global challenges with faith-driven innovation.